Evolución del índice y su influencia en los rendimientos de los portafolios de inversiones en los fondos privados de pensiones 2014-2018 (2020)
This paper aims to provide an explanation of the relationship between the COLCAP index and private pension funds during the aforementioned period. Starting from an analysis of the COLCAP index as well as an explanation of the Colombian pension system and the private funds that it has. A practical analysis was also carried out using an econometric model that helped support the theoretical contribution that was worked throughout the research.